Dr. Ashley Tregaskiss — Deep Plane Facelift — Vancouver - Tregaskiss, Ashley (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Ashley Tregaskiss, practicing in Vancouver, Canada. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003426; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; canada; vancouver